PENGELOLAAN LINGKUNGAN KERJA DAN KEPUASAN KERJA PENGARUHNYA TERHADAP KOMITMEN KARYAWAN PT.DM INTERNATIONAL - David Panjaitan; Suhardoyo (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Managing human resources based on the ability of employees will be able to guarantee the success of an organization or company in achieving the goals set. The company’s ability to create employee commitment in the organization is needed as well as the work environment and job satisfaction needs to be created as important because it has a great influence on the death of the company. For this reason, this study wants to see how much influence the work environment and employee satisfaction in creating employee commitment at PT. DM International. This type of research is explanatory research, with a population of 100 employees in this study, the determination of the number of samples using the Slovin formula with a sample of 80 employees. Determination of the sample using purposive sampling technique, this study was analyzed through Linear Regression Analysis with the help of SPSS 23 software. The results showed the work environment had an effect on employee commitment of 0.221. so that the work environment is supported by good lighting or light, good air circulation, without any noise and odor and safety in the workplace so that it will increase employee commitment which will further influence employee performance. Job Satisfaction influences employee commitment by 0.421. Employees who have job satisfaction will work with a maximum and full of initiative so that work results seen in quality and quantity of work will show maximum results. Thus employees will increase their commitment to the company and continue to survive with the ability to carry out tasks and responsibilities if supported by work environment conditions and job satisfaction felt by employees. Employees will feel that they own the company so they will continue to maintain the company’s survival